The impact of globalization on domestic employment - Hao Wei; Linlin Deng; Peng Zhou (Cardiff University, Cardiff Business School, 2022)
Immigrants and offshore workers become important disturbing factors of domestic employment in the globalized economy. In this study we build a model with this feature to test how the three groups of workers in the labor force interact using a panel data of 155 countries over the period 1990-2015. We find that while immigrants replaced native workers (especially highly skilled ones), offshore workers who produce intermediate input imports do not. The productivity effect of offshoring is stronger for developed economies while the substitution effect of immigration is stronger for developing countries. Furthermore, the productivity effects of immigration and offshoring are stronger when governments impose less restrictions on international trade and domestic labor market.
Keywords: 330; immigration; offshoring; intermediate input imports; domestic employment; skill-bias effect